2011
DOI: 10.1039/c1cc13096j
|View full text |Cite
|
Sign up to set email alerts
|

Nickel(ii) oxide surface-modified titanium(iv) dioxide as a visible-light-active photocatalyst

Abstract: The electronic modification of TiO(2) with highly dispersed NiO particles smaller than ca. 2 nm by the chemisorption-calcination-cycle technique has given rise to a high level of visible-light-activity exceeding that of iron oxide-surface modified TiO(2) simultaneously with the UV-light-activity being significantly increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 23 publications
4
55
0
Order By: Relevance
“…Similar shifts in the VB edge for other metal oxide-nanocluster modified TiO 2 are explained on the basis of the formation of new VB states coming from the oxide nanocluster. [17][18][19][20][21] This interfacial electron transfer causes efficient charge carrier separation contributing to the increases in the photocatalytic activities and the reduction in the TiO 2 Figure 12. Atomic structure, adsorption energy in eV and Ti 3d and Cu 3d projected electronic density of states (PEDOS) for anatase TiO2 modified with CuO, Cu2O2 and Cu4O4 clusters Figure 11.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar shifts in the VB edge for other metal oxide-nanocluster modified TiO 2 are explained on the basis of the formation of new VB states coming from the oxide nanocluster. [17][18][19][20][21] This interfacial electron transfer causes efficient charge carrier separation contributing to the increases in the photocatalytic activities and the reduction in the TiO 2 Figure 12. Atomic structure, adsorption energy in eV and Ti 3d and Cu 3d projected electronic density of states (PEDOS) for anatase TiO2 modified with CuO, Cu2O2 and Cu4O4 clusters Figure 11.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported that FeO x and NiO cluster-surface modified TiO 2 prepared by the chemisorption-calcination cycle (CCC) technique shows high photocatalytic activities under illumination of visible-and UV-light. [17][18][19][20][21] In both the systems, strong dependence of the photocatalytic activity on the loading amount of the clusters is observed, [17][18][19][20][21] but the reason has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have shown that the surface modification of anatase and anatase/rutile TiO 2 , having the highest level of UV-light activity among the commercial ones, with iron oxide [31] and nickel oxide clusters [32] by the chemisorptioncalcination cycle (CCC) technique yields a high level of visiblelight activity and a concomitant increase in the UV-light activity. In contrast, the surface modification by molecular SnO 2 affords no visible-light activity, while the UV-light activity does increase.…”
Section: Introductionmentioning
confidence: 99%
“…5C). It has been demonstrated that the surface modification of TiO 2 by a certain amount of Ni(OH) 2 /NiO clusters may enhance the photocatalytic activity of TiO 2 , but the excess loading can result in the reduction of the photocatalytic activity [42,43]. In the present investigation, the loading of a large amount of Ni(OH) 2 in the intervals of the TiO 2 nanorods is responsible for decrease in the photocatalytic activity of the composite film electrode.…”
Section: Resultsmentioning
confidence: 75%